Between a rock-a-bye and a hard place: mood disorders during the peripartum period. (19th January 2018) - Thomson, Michael; Sharma, Verinder
Abstract : Mood disorders including major depressive disorder and bipolar disorder are common during and after pregnancy. Timely identification and appropriate management of mood episodes is essential to maximize maternal well-being and minimize adverse outcomes. Failure to do so results in maternal suffering and impaired child bonding, and has the potential for devastating outcomes including suicide and infanticide. Women are routinely screened for unipolar depression during or after pregnancy but not for bipolar disorder, in spite of the fact that childbirth is associated with a major risk for onset or exacerbation of bipolar disorder. Delays in detection as well as misdiagnosis of bipolar disorder as major depressive disorder may put women at risk of many adverse consequences, including symptom exacerbation, psychiatric hospitalization, and suicide. A thorough psychiatric assessment is necessary to establish diagnosis, to address safety issues, and to formulate a treatment plan. Treatment of mood disorders during pregnancy is complicated by the potential risks of fetal exposure to psychotropic medications, and the use of these medications during the postpartum period may result in infant medication exposure through breastmilk. These risks of psychotropic medication exposure must be weighed against the risk of untreated mood disorders. This review will discuss the pathophysiology, epidemiology, diagnosis, and treatment of mood disorders during pregnancy and the postpartum period. Screening tools that can be used in the primary care and obstetrics settings to assist in identifying women with peripartum mood disorders will also be discussed.